FAKTOR–FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS RAWAT INAP WAY HALIM II KOTA BANDAR LAMPUNG - Mirah Widhisastri, IGA; Indrasari, Nelly; Susanti, Susi (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Anemia in pregnancy is defined as having hemoglobin levels below 11 g/dl. This condition can lead to various complications during pregnancy and childbirth, including an increased risk of fetal death in the womb. In Indonesia, the prevalence of anemia among pregnant women is notably high, with approximately 48.9% affected. These figures indicate that anemia is a significant public health issue in the country, as it exceeds the threshold of 40% prevalence, which is considered severe. The purpose of this study was to examine the relationship between various factors and the incidence of anemia in pregnant women within the Way Halim II Inpatient Health Center's work area in Bandar Lampung City. This research utilized quantitative methods, specifically an observational analytic design with a case-control approach. The Chi-Square statistical test was employed for analysis. The study included a sample of 80 pregnant women, divided into two groups: 40 women who were diagnosed with anemia and 40 who were not. Data for the study were collected from secondary sources, specifically from Maternal and Child Health (MCH) register records. The results indicated a significant relationship between maternal age and the incidence of anemia (p value 0.000) as well as nutritional status (p value 0.001). However, there was no significant relationship between parity and the incidence of anemia in pregnant women (p value 1.000). In conclusion, maternal age and nutritional status are associated with the incidence of anemia in pregnant women, while parity does not appear to have an effect. It is recommended that health workers routinely monitor the administration of iron (Fe) tablets and provide counseling on their importance to help prevent anemia in pregnant women